The impact of mobile money on financial inclusion in Lesotho - Tsemane, Alex (University of the Free State, 2015)
The key purpose of the research was to find the positive effect that the advent of mobile money brought to Lesotho with regard to financial inclusion. The research was prompted by the increasing integration of mobile money service in the everyday lives of Lesotho citizens from bill payments to mobile top-up to transfers and many other services which were traditionally available through mainstream banks. Many Basotho had been excluded from the formal economy due to the high cost of conventional banking. The government, together with other world NGOs, have tried to increase the levels of financial inclusion but not according to their targets. Thus the arrival of mobile money has been hailed as the ideal solution for Lesotho given its level of economic development and its hard-to-traverse mountainous terrain. Various challenges and benefits of mobile money were also investigated alongside the primary objective. A quantitative approach was followed in this study in order to unravel the extent of mobile money adoption in the country. Structured questionnaires were distributed to both the lowlands, semi-lowlands, and highland parts of the country. Various tools were used to find elements such as frequencies of major variables and the interrelation between them in order to understand more about this great East African innovation in Southern Africa. It was found out that most Basotho use mobile money to perform key services such as bill payments, cash-ins and cash-outs. It was also found out that larger sums of money were transacted across the platforms despite the general perception that the mobile money service was formulated for small amounts of money. It was also found that mobile money offered many advantages. These included safety, privacy, convenience, ease of use and registration. The greatest challenge to this innovation was found to be liquidity problems at the agents which are vital for the success of mobile money. It was concluded that mobile money is gaining momentum to become part of the cashless society that is so popular in developed countries. In addition to the system being popular, there are indeed challenges for the platform which can be overcome through some or part of the recommendations. This would then considerably increase the uptake of mobile money in Lesotho.
Dissertation (MBA (Business Administration))--University of the Free State, 2015
Keywords: Mobile money; Financial inclusion; Mobile money agent; Phone; Mobile network operator; Telecommunications; Banking; Subscriber; Regulator; Mobile apps -- Lesotho; Banks and banking, Mobile -- Lesotho; Cell phones -- Lesotho